Large-size boron carbide-graphene composite ceramic as well as preparation method and application thereof
Through a current sintering system with vacuum induction and pulsed dual-mode heating, the dual-mode mode of hot press sintering and discharge plasma sintering is adopted to solve the problems of uneven microstructure and insufficient density in the preparation of large-size boron carbide-graphene composite ceramics, and the preparation of materials with high density and excellent mechanical properties is achieved.
Patent Information
- Application Number
- CN202411725168.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Traditional sintering methods are difficult to achieve the uniform microstructure and high density of large-size boron carbide-graphene composite ceramics, resulting in poor mechanical properties of the materials.
A large-size boron carbide-graphene composite ceramic is prepared by a dual-mode mode of hot press sintering and discharge plasma sintering through a dual-mode mode of hot press sintering and discharge plasma sintering for 5 to 10 minutes at a sintering temperature of 1800~2000℃.
The high density and uniform microstructure of large-size boron carbide-graphene composite ceramics are achieved, and its bending strength and fracture toughness are improved.
Smart Images

Figure CN119591408A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic materials, and in particular relates to a large-size boron carbide-graphene composite ceramic and a preparation method and application thereof. Background Art
[0002] Boron carbide ceramics have the remarkable characteristics of low density and high hardness. They have important application value in bulletproof equipment, aerospace and national defense construction, and are an important dual-use impact protection material for both military and civilian use. However, due to the strong covalent bond and low self-diffusion coefficient of boron carbide, the material densification temperature is relatively high (hot pressing sintering temperature ≥ 2100℃) and the fracture toughness is relatively low (2.2MPa·m 1 / 2 These shortcomings seriously limit the widespread application of boron carbide ceramic materials in the engineering field.
[0003] As the most popular new carbon material in current research, graphene has been proven to be an ideal reinforcement material for boron carbide ceramics. It can simultaneously improve the mechanical and electrical properties of boron carbide, thereby realizing the processing of high-performance special-shaped boron carbide ceramic components. However, the traditional sintering method is difficult to achieve the uniformity and stability of the microstructure of large-scale high-performance boron carbide-graphene composite ceramics. Hot pressing sintering (HP) has the advantage of uniform temperature field distribution, but high-temperature and long-term hot pressing sintering will not only lead to coarsening of boron carbide ceramic grains, but also graphitization of graphene located on the boron carbide grain boundary, both of which are not conducive to improving the mechanical properties of boron carbide-graphene composite ceramics. Spark plasma sintering (SPS) has the advantages of fast heating rate and short holding time, which can effectively avoid the damage of graphene to high-temperature and long-term heat treatment. However, due to the uneven distribution of SPS sintering temperature field, a large temperature gradient is caused in the radial direction, which limits the uniformity and stability of the material structure. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a large-sized boron carbide-graphene composite ceramic and its preparation method and application. The present invention uses graphene nanosheets and boron carbide powder as raw materials, and utilizes the "current sintering system with radiation heating device" disclosed in Chinese patent CN101050121A to achieve vacuum induction and pulse dual-mode heating, and successfully obtains large-sized boron carbide-graphene composite ceramics at a sintering temperature of 1800-2000°C for 5-10 minutes. The composite ceramic prepared by the present invention has fine grains, high density and uniform microstructure, and has high bending strength and fracture toughness.
[0005] The purpose of the present invention is achieved through the following technical solutions: A large-sized boron carbide-graphene composite ceramic with high density and uniform microstructure, with a size of 17~22cm and a density of 2.502~2.518 g / cm 3 , Vickers hardness is 31.5~33.8 GPa, bending strength is 462~536MPa, fracture toughness is 3.86~4.73 MPa·m 1 / 2 .
[0006] Preferably, the Vickers hardness is 33.5-33.8 GPa, the bending strength is 515-536 MPa, and the fracture toughness is 4.62-4.73 MPa·m 1 / 2 .
[0007] The preparation method of the above-mentioned large-size boron carbide-graphene composite ceramic comprises the following steps: (1) uniformly dispersing graphene in ethanol to obtain a graphene dispersion; adding boron carbide to the graphene dispersion, stirring and ultrasonicating, and then ball milling, drying and sieving to obtain a composite ceramic powder; (2) The composite ceramic powder of step (1) is compacted and placed in a sintering furnace, and a protective atmosphere is introduced. Hot pressing sintering is first performed, the temperature is raised to 1200-1500° C. and kept at this temperature for 15-45 min, and then spark plasma sintering is performed simultaneously, the temperature is further raised to 1800-2000° C. and kept at this temperature for 5-15 min, and finally naturally cooled to obtain a large-sized boron carbide-graphene composite ceramic.
[0008] Preferably, in step (1), in terms of mass percentage, graphene accounts for 0.5-4wt% of the total mass of boron carbide and graphene, and boron carbide accounts for 96-99.5wt% of the total mass of boron carbide and graphene.
[0009] Preferably, in step (1), the thickness of the graphene is 1-5 nm, and the sheet size is 3-10 μm.
[0010] Preferably, in step (1), the purity of boron carbide is greater than 97% and the particle size is 0.5-3 μm.
[0011] Preferably, in step (1), the concentration of the graphene dispersion is 1-5 mg / mL.
[0012] Preferably, in step (1), the ultrasonic conditions are: ultrasonic power is 800-1000W, and ultrasonic time is 1-3h.
[0013] Preferably, in step (1), the stirring conditions are: a stirring rate of 200-500 rpm / min, and a stirring time of 1-3 h.
[0014] Preferably, in step (1), the ball milling conditions are: a planetary ball mill is used, the grinding balls are SiC balls, the ball-to-material ratio is (2-10):1, the ball milling speed is 100-300 rpm / min, and the ball milling time is 12-36h.
[0015] Preferably, in step (1), the drying conditions are: drying in a vacuum drying oven, the drying temperature is 60° C., and the drying time is 24 to 48 hours.
[0016] Preferably, in step (1), the mesh size of the sieve is 100-325 meshes.
[0017] Preferably, in step (2), the protective atmosphere is argon.
[0018] Preferably, in step (2), the hot pressing sintering conditions are: heating to 1200-1500° C. at a heating rate of 5-20° C. / min and a pressure of 3-10 MPa.
[0019] Preferably, in step (2), the conditions for spark plasma sintering are: heating to 1800-2000° C. at a heating rate of 50-100° C. / min and a pressure of 20-60 MPa.
[0020] The application of the above-mentioned large-size boron carbide-graphene composite ceramics in the engineering field.
[0021] The principles involved in the present invention include the following: First, the preparation of large-sized boron carbide-graphene composite ceramics is very difficult. The mechanism of HP sintering is to radiate and diffuse heat from the outside to the inside through the heating element. Therefore, the temperature is higher near the heating element, while the temperature is lower away from the heating element. This temperature gradient distribution usually leads to high density in the periphery of large-sized ceramic components and low density in the center. The mechanism of SPS sintering is to discharge ceramic ions through a large current to generate Joule heat for heating. The peripheral resistance of large-sized ceramic components is large, resulting in a small current passing through, so the temperature and heat are also low. Therefore, the characteristic of SPS sintering is that the product has a high center density and a low edge density. Combining the sintering characteristics of the two sintering methods, the large-sized boron carbide-graphene composite ceramics sintered by dual-mode sintering are in a uniform temperature field, with a dense structure and the rapid heating and short-term heat preservation of high-temperature SPS can ensure that the grains of boron carbide ceramics do not grow abnormally, and realize the rapid preparation of large-sized dense and fine-grained boron carbide ceramics.
[0022] Second, graphene with excellent mechanical and electrical properties will usually be graphitized under the condition of high temperature and long-term heat preservation treatment, causing it to denature, thereby affecting the mechanical properties of graphene-reinforced boron carbide ceramics. In the present invention, the relatively uniform temperature field of HP sintering at low temperature is first utilized, and a certain temperature is raised at a lower heating rate, and this temperature does not cause any damage to the structure of graphene. In the high temperature stage, HP and SPS sintering modes are used at the same time, which not only ensures the uniformity of the temperature field, but also realizes the densification of boron carbide-graphene ceramics in a shorter time, while also maintaining the integrity of the graphene structure, and realizing the rapid preparation of high-performance boron carbide-graphene composite ceramics.
[0023] Compared with the prior art, the beneficial effects of the present invention include: (1) The present invention solves the problem of preparing large-sized boron carbide-graphene composite ceramics by using a dual-mode sintering furnace.
[0024] (2) The boron carbide-graphene composite ceramic prepared by the present invention using dual-mode sintering (using HP and SPS sintering modes simultaneously) has fine grains and a complete graphene structure, which is beneficial to improving the mechanical properties of the material.
[0025] (3) In the high temperature stage of the present invention, the SPS heating rate is fast and the heat preservation time is short. Compared with traditional hot pressing and long-time pressureless sintering, the power loss is small and the cost is lower.
[0026] (4) The sintering method provided by the present invention has simple procedures, good repeatability, high stability, and is easy to realize industrialization and batch stable production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a real photo of the large-sized boron carbide-graphene composite ceramic prepared by the present invention.
[0028] Figure 2 This is a fracture morphology image of the boron carbide-graphene composite ceramic prepared in Example 1.
[0029] Figure 3 This is a transmission electron microscope image of the boron carbide-graphene composite ceramic prepared in Example 1, wherein a and b are transmission electron microscope images at different magnification ratios.
[0030] Figure 4 This is a fracture morphology image of the boron carbide-graphene composite ceramic prepared in Example 2.
[0031] Figure 5 The fracture morphology (left) and Raman spectrum (right) of the boron carbide-graphene composite ceramic prepared in Comparative Example 1.
[0032] Figure 6This is the fracture morphology of the boron carbide-graphene composite ceramic prepared in Comparative Example 2. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Example 1 A method for preparing a large-size boron carbide-graphene composite ceramic, the steps are as follows: (1) Preparation of graphene dispersion: adding graphene powder to alcohol, dispersing by ultrasonication and mechanical stirring, with an ultrasonic power of 1000 W, a stirring speed of 200 rpm / min, and a dispersion treatment time of 2 h to obtain a uniformly dispersed graphene dispersion; (2) Preparation of boron carbide-graphene composite ceramic powder: Add boron carbide powder to the graphene dispersion prepared in step (1), the mass percentage of boron carbide and graphene are 98%:2%, respectively, stir and ultrasonicate at a stirring speed of 200 rpm / min for 2 hours; then perform planetary ball milling, the grinding balls are SiC balls, the ball-to-material ratio is 4:1, the speed of high-energy planetary ball milling is 200 rpm / min, and the ball milling time is 24 hours. After the ball milling, the sample is placed at 60°C and dried for 24 hours, and then passed through a 200-mesh sieve to obtain a fine-grained, evenly dispersed boron carbide-graphene mixed powder.
[0035] (3) The boron carbide-graphene mixed powder obtained in step (2) is loaded into a graphite mold and compacted. The inner wall of the graphite mold, the pressure head and the powder are separated by graphite paper. Then, it is placed in an electric current sintering system with a radiation heating device, and argon gas is introduced as a protective atmosphere. The specific sintering system is as follows: low temperature stage, hot pressing sintering: heating to 1200°C at a heating rate of 8°C / min, pressure of 10 MPa, and keeping warm for 30 min; then, the SPS sintering mode is turned on at the same time, heating to the target temperature of 2000°C at a heating rate of 100°C / min, pressure of 30 MPa, keeping warm for 10 min, and then naturally cooling.
[0036] The physical structure of the large-scale boron carbide-graphene composite ceramic prepared in Example 1 was observed using a scanning electron microscope. The observation results are as follows: Figure 2 See Figure 2 We all know that dual-mode sintering can obtain nearly completely dense boron carbide-graphene composite ceramic materials under the sintering conditions of 2000℃ high temperature and 30 MPa insulation for 10 min. Compared with hot pressing sintering, the grains of boron carbide are finer. In addition, Figure 3This is a cross-sectional microstructure diagram of the large-sized boron carbide-graphene composite ceramic prepared in Example 1. Figure 3 It can be seen that the graphene nanosheets with lamellar structure are evenly distributed on the grain boundaries of boron carbide ceramics.
[0037] Furthermore, the boron carbide-graphene composite ceramic disc prepared in Example 1 was divided into sectors of different sizes along the radial direction, and the mechanical properties of the materials in different regions were tested. The results showed that the density and mechanical properties of the materials in different positions were very small. According to statistics, the average properties of the composite ceramic samples prepared in this example are as follows: the density is 2.517 g / cm 3 , Vickers hardness is 33.5GPa, bending strength is 515 MPa, fracture toughness is 4.62 MPa·m 1 / 2 .
[0038] Example 2 A method for preparing a large-size boron carbide-graphene composite ceramic, the steps are as follows: (1) Preparation of graphene dispersion: adding graphene powder to alcohol, dispersing by ultrasonication and mechanical stirring, with an ultrasonic power of 800 W, a stirring speed of 250 rpm / min, and a dispersion treatment time of 2 h to obtain a uniformly dispersed graphene dispersion; (2) Preparation of boron carbide-graphene composite ceramic powder: Add boron carbide powder to the graphene dispersion prepared in step (1), with the mass percentage of boron carbide and graphene being 99%:1% respectively, and stir while ultrasonicating at a stirring speed of 300 rpm / min for 2 hours; then perform planetary ball milling, with SiC balls as grinding balls, a ball-to-material ratio of 4:1, a high-energy planetary ball milling speed of 300 rpm / min, and a ball milling time of 24 hours. After the ball milling, dry the sample at 60°C for 24 hours, and pass through a 200-mesh sieve to obtain a fine-grained, evenly dispersed boron carbide-graphene mixed powder.
[0039] (3) The boron carbide-graphene mixed powder obtained in step (2) is loaded into a graphite mold and compacted. The inner wall of the graphite mold, the pressure head and the powder are separated by graphite paper. Then, it is placed in an electric current sintering system with a radiation heating device, and argon gas is introduced as a protective atmosphere. The specific sintering system is as follows: low temperature stage, hot pressing sintering: heating to 1500°C at a heating rate of 8°C / min, pressure of 10 MPa, and keeping warm for 30 min; then, the SPS sintering mode is turned on at the same time, heating to the target temperature of 1980°C at a heating rate of 50°C / min, pressure of 30 MPa, keeping warm for 10 min and then cooling naturally.
[0040] The physical structure of the large-scale boron carbide-graphene composite ceramic prepared in Example 2 was observed using a scanning electron microscope. The observation results are as follows: Figure 4 See Figure 4 We all know that under the sintering conditions of 1980℃ and 30 MPa for 10 min, nearly completely dense boron carbide-graphene composite ceramic materials can be obtained by dual-mode sintering. Unlike Example 1, the graphene content in Example 2 is lower, and it is difficult to observe the presence of graphene in the boron carbide ceramic substrate through a microscope. There are two main reasons. On the one hand, some graphene will react with a small amount of boron oxide impurities on the surface of boron carbide ceramics; on the other hand, graphene nanosheets are very thin, and when the content is low, it is difficult to observe it at a low magnification through a transmission electron microscope due to the low resolution of the equipment.
[0041] Similarly, the boron carbide-graphene composite ceramic disc prepared in Example 2 was divided into sectors of different sizes along the radial direction, and the mechanical properties of the materials in different regions were tested. The results showed that the density and mechanical properties of the materials in different positions were not much different. According to statistics, the average properties of the composite ceramic samples prepared in this example are as follows: the density is 2.518 g / cm 3 , Vickers hardness is 33.8 GPa, bending strength is 536 MPa, and fracture toughness is 4.73 MPa·m 1 / 2 .
[0042] Example 3 A method for preparing a large-size boron carbide-graphene composite ceramic, the steps are as follows: (1) Preparation of graphene dispersion: adding graphene powder to alcohol, dispersing by ultrasonication and mechanical stirring, with an ultrasonic power of 1000 W, a stirring speed of 200 rpm / min, and a dispersion treatment time of 2 h to obtain a uniformly dispersed graphene dispersion; (2) Preparation of boron carbide-graphene composite ceramic powder: Add boron carbide powder to the graphene dispersion prepared in step (1), with the mass percentage of boron carbide and graphene being 96%:4% respectively, and stir while ultrasonicating at a stirring speed of 250 rpm / min for 2 hours; then perform planetary ball milling, with SiC balls as grinding balls, a ball-to-material ratio of 4:1, a high-energy planetary ball milling speed of 250 rpm / min, and a ball milling time of 24 hours. After the ball milling, dry the sample at 60°C for 24 hours, and pass through a 200-mesh sieve to obtain a fine-grained, evenly dispersed boron carbide-graphene mixed powder.
[0043] (3) The boron carbide-graphene mixed powder obtained in step (2) is loaded into a graphite mold and compacted. The inner wall of the graphite mold, the pressure head and the powder are separated by graphite paper. Then, it is placed in an electric current sintering system with a radiation heating device, and argon gas is introduced as a protective atmosphere. The specific sintering system is as follows: low temperature stage, hot pressing sintering: heating to 1350°C at a heating rate of 8°C / min, pressure of 10 MPa, and keeping warm for 30 min; then, the SPS sintering mode is turned on at the same time, heating to the target temperature of 2000°C at a heating rate of 100°C / min, pressure of 30 MPa, keeping warm for 10 min, and then naturally cooling.
[0044] The boron carbide-graphene composite ceramic disc prepared in Example 3 was divided into sectors of different sizes along the radial direction, and the mechanical properties of the materials in different regions were tested. According to statistics, the average properties of the composite ceramic samples prepared in this example are as follows: density is 2.502 g / cm 3 , Vickers hardness is 31.5GPa, bending strength is 462MPa, fracture toughness is 3.86MPa·m 1 / 2 .
[0045] Comparative Example 1 A hot pressing and sintering preparation method of boron carbide-graphene composite ceramics, the steps are as follows: (1) Preparation of graphene dispersion: adding graphene powder to alcohol, dispersing by ultrasonication and mechanical stirring, with an ultrasonic power of 1000 W, a stirring speed of 200 rpm / min, and a dispersion treatment time of 2 h to obtain a uniformly dispersed graphene dispersion; (2) Preparation of boron carbide-graphene composite ceramic powder: Add boron carbide powder to the graphene dispersion prepared in step (1), with the mass percentage of boron carbide and graphene being 98.5%:1.5% respectively, and stir while ultrasonicating at a stirring speed of 300 rpm / min for 2 hours; then perform planetary ball milling, with SiC balls as grinding balls, a ball-to-material ratio of 4:1, a high-energy planetary ball milling speed of 200 rpm / min, and a ball milling time of 24 hours. After the ball milling, dry the sample at 60°C for 24 hours, and pass through a 200-mesh sieve to obtain a fine-grained, evenly dispersed boron carbide-graphene mixed powder.
[0046] (3) The boron carbide-graphene mixed powder obtained in step (2) is placed in a graphite mold and compacted. The inner wall of the graphite mold, the pressure head and the powder are separated by graphite paper. Then, the mold is placed in a hot pressing furnace. When the vacuum in the furnace is evacuated to 3×10 - 3When the pressure is below 0.04 Pa, the equipment start-up conditions are met. First, an axial pressure of 30 MPa is applied to the sample, and the temperature is raised from room temperature to 1200°C at a heating rate of 10°C / min. Ar gas is filled in, and then the temperature is further raised from 1200°C to 2000°C at a heating rate of 5°C / min. Finally, it is kept at this temperature for 1 h.
[0047] The physical structure of the boron carbide-graphene composite ceramic prepared in Comparative Example 1 was observed using a scanning electron microscope. Figure 5 shown. Figure 5 The fracture morphology and Raman spectrum of the boron carbide-graphene composite ceramic prepared in Comparative Example 1; see Figure 5 We all know that hot pressing sintering at 2000℃ and 30 MPa for 1 h can obtain almost completely dense boron carbide-graphene composite ceramic materials. It is not difficult to find that the grains of boron carbide ceramics are relatively coarse. In addition, the microstructure of the cross section of boron carbide ceramics shows that there are no obvious graphene nanosheets on the boron carbide grain boundaries. This phenomenon can also be confirmed from its Raman spectrum. It is generally believed that the D, G and 2D peaks of GNPs (graphene) are located at 1340 cm -1 , 1586 cm -1 and 2660 cm -1 The ratio of the intensity of the 2D peak to the intensity of the G peak is usually used to reflect the thickness of the graphene nanosheet layer. In the Raman spectrum of this comparative example, the intensity of the 2D peak is weak and the peak width is large, indicating that the graphene nanosheet has been graphitized under the condition of long-term heat preservation during hot pressing.
[0048] After testing, the properties of the composite ceramic sample prepared in Comparative Example 1 are as follows: density is 2.515 g / cm 3 , Vickers hardness is 32.3 GPa, bending strength is 428 MPa, and fracture toughness is 2.76 MPa·m 1 / 2 .
[0049] Comparative Example 2 A method for preparing boron carbide-graphene composite ceramic by spark plasma sintering, the steps are as follows: (1) Preparation of graphene dispersion: adding graphene powder to alcohol, dispersing by ultrasonication and mechanical stirring, with an ultrasonic power of 1000 W, a stirring speed of 200 rpm / min, and a dispersion treatment time of 1 h to obtain a uniformly dispersed graphene dispersion; (2) Preparation of boron carbide-graphene composite ceramic powder: Add boron carbide powder to the graphene dispersion prepared in step (1), with the mass percentage of boron carbide and graphene being 98%:2% respectively, and stir while ultrasonicating at a stirring speed of 300 rpm / min for 2 hours; then perform planetary ball milling, with SiC balls as grinding balls, a ball-to-material ratio of 4:1, a high-energy planetary ball milling speed of 150 rpm / min, and a ball milling time of 24 hours. After the ball milling, dry the sample at 60°C for 24 hours, and pass through a 200-mesh sieve to obtain a fine-grained, evenly dispersed boron carbide-graphene mixed powder.
[0050] (3) The boron carbide-graphene mixed powder obtained in step (2) is loaded into a graphite mold and compacted. The inner wall of the graphite mold, the pressure head and the powder are separated by graphite paper. Then, the mold is placed in a spark plasma sintering furnace. An axial pressure of 50 MPa is first applied to the sample. When the vacuum in the furnace is evacuated to below 3×10-3 Pa, the equipment startup condition is met. The equipment is heated from room temperature to 600°C within 5 minutes, and then heated to 1800°C at a heating rate of 100°C / min. Finally, the temperature is kept at this temperature for 10 minutes.
[0051] The physical structure of the boron carbide-graphene composite ceramic prepared in Comparative Example 2 was observed using a scanning electron microscope. Figure 6 See Figure 6 We all know that the structure of boron carbide-graphene composite ceramic materials prepared by spark plasma sintering at 1800℃ and 50 MPa for 10 min is not uniform. Specifically, the structure of the central part of the ceramic product is dense and the graphene nanosheets are evenly distributed in the boron carbide ceramic matrix, but some pores are found locally near the edge of the ceramic sheet, which is related to the inherent defects of the spark plasma sintering furnace.
[0052] The ceramic disc is divided into sectors of different sizes along the radial direction of the ceramic disc, and the mechanical properties of the materials in different regions are tested. According to statistics, the average properties of the composite ceramic samples prepared in this comparative example are as follows: density is 2.42 g / cm 3 , Vickers hardness is 28.2 GPa, bending strength is 327 MPa, and fracture toughness is 2.96 MPa·m 1 / 2 .
[0053] Figure 1 This is a photo of the large-sized boron carbide-graphene composite ceramic prepared by the present invention. Figure 1It can be seen that the boron carbide-graphene composite ceramic prepared by the present invention has a size of up to 17 cm and is intact without cracks, which has important practical significance for improving material performance, reducing production costs, expanding the scope of application, and promoting the industrialization process. Note that the actual photo of the boron carbide-graphene composite ceramic prepared in Example 1 is used as a representative, and the size of the composite ceramics prepared in Examples 2 to 3 is basically the same as that in Example 1, and is also intact without cracks.
[0054] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A large-size boron carbide-graphene composite ceramic, characterized in that: It has high density and uniform microstructure, with a size of 17~22cm and a density of 2.502~2.518 g / cm 3 , Vickers hardness is 31.5~33.8 GPa, bending strength is 462~536 MPa, fracture toughness is 3.86~4.73 MPa·m 1 / 2 .
2. The large-size boron carbide-graphene composite ceramic according to claim 1, characterized in that: The Vickers hardness is 33.5~33.8 GPa, the bending strength is 515~536 MPa, and the fracture toughness is 4.62~4.73 MPa·m 1 / 2 .
3. The method for preparing the large-size boron carbide-graphene composite ceramic according to any one of claims 1 to 2, characterized in that: The steps include: (1) uniformly dispersing graphene in ethanol to obtain a graphene dispersion; adding boron carbide to the graphene dispersion, stirring and ultrasonicating, and then ball milling, drying and sieving to obtain a composite ceramic powder; (2) The composite ceramic powder of step (1) is compacted and placed in a sintering furnace, and a protective atmosphere is introduced. Hot pressing sintering is first performed, the temperature is raised to 1200-1500° C. and the temperature is kept for 15-45 min, and then spark plasma sintering is performed simultaneously, the temperature is further raised to 1800-2000° C. and the temperature is kept for 5-15 min, and finally naturally cooled to obtain the large-sized boron carbide-graphene composite ceramic.
4. The method for preparing the large-size boron carbide-graphene composite ceramic according to claim 3, characterized in that: In step (1), in terms of mass percentage, graphene accounts for 0.5-4wt% of the total mass of boron carbide and graphene, and boron carbide accounts for 96-99.5wt% of the total mass of boron carbide and graphene; The concentration of the graphene dispersion in step (1) is 1-5 mg / mL.
5. The method for preparing the large-size boron carbide-graphene composite ceramic according to claim 4, characterized in that: The graphene in step (1) has a thickness of 1-5 nm and a sheet diameter of 3-10 μm; The purity of the boron carbide in step (1) is greater than 97%, and the particle size is 0.5-3 μm.
6. The method for preparing the large-size boron carbide-graphene composite ceramic according to claim 3, characterized in that: The ultrasonic conditions in step (1) are as follows: the ultrasonic power is 800-1000W and the ultrasonic time is 1-3h; The stirring conditions in step (1) are: a stirring rate of 200-500 rpm / min and a stirring time of 1-3 h.
7. The method for preparing the large-size boron carbide-graphene composite ceramic according to claim 3, characterized in that: The ball milling conditions in step (1) are as follows: a planetary ball mill is used, the grinding balls are SiC balls, the ball-to-material ratio is (2-10):1, the ball milling speed is 100-300 rpm / min, and the ball milling time is 12-36 hours; The drying conditions of step (1) are: drying in a vacuum drying oven, the drying temperature is 60° C., and the drying time is 24 to 48 hours.
8. The method for preparing the large-size boron carbide-graphene composite ceramic according to claim 7, characterized in that: The mesh size of the sieving in step (1) is 100-325 mesh; The protective atmosphere in step (2) is argon.
9. The method for preparing the large-size boron carbide-graphene composite ceramic according to any one of claims 3 to 7, characterized in that: The hot pressing sintering conditions in step (2) are: heating to 1200-1500° C. at a heating rate of 5-20° C. / min and a pressure of 3-10 MPa; The conditions for the spark plasma sintering in step (2) are: heating to 1800-2000° C. at a heating rate of 50-100° C. / min and a pressure of 20-60 MPa.
10. Application of the large-size boron carbide-graphene composite ceramic according to any one of claims 1 to 2 in the field of engineering.
Citation Information
Patent Citations
Dual heating mode flash sintering method combining current heating with radiant heating
CN101050121A
Graphene / boron carbide ceramic composite material and preparation method thereof
CN107555995A
Preparation method of boron carbide ceramic chips
CN107840661A
Preparation method of graphene / boron carbide ceramic composite material
CN108383527A
High-strength SiC composite ceramic and preparation method thereof
CN116621585A